Studi Kasus Jajanan yang Mengandung Boraks dan Formalin di Taman Kurma Kota Lubuklinggau - Nopa Nopiyanti; Yuni Krisnawati; Septi Heriani (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
The research objective was to find out borax and formalin content in snacks at Lubuklinggau palm trees citypark. The research was a qualitative descriptive research with snacks samples as the object of the research. The data collection was conducted through observation and documentation. The data were analyzed qualitatively through borax and formalin test content by using test kit. The color change on yellow paper test turned into red brownies indicated a positive result of borax content and the color change in the liquid into purple indicated formalin content. The result of the test content with borax and formalin test kit on 187 samples showed the negative result on borax content. The test on formalin content indicated that there were 22 samples that use formalin such as 15 sausage samples, 2 noodle samples, 4 meatball samples and 1 tofu sample. Based on the research result, it can be concluded that the tested samples contain zero borax. In contrast, some snacks contain formalin, such as sausages, noodles, meatballs and fried tofu found at some street vendors. Keywords: snacks , borax, formalin, test kit.